Conservation and restoration of the cast plaster gallery at the Escuela de Artes Plásticas (school of fine arts) at the University of Costa Rica - Zamora Rodríguez, Herbert (2014)
This article examines the status of one of the oldest plaster cast collections at the Escuela de Artes Plásticas (School of Fine Arts) at the University of Costa Rica.  This plaster cast gallery dates from 1897 and the Costa Rican government acquired it as a teaching tool for academic development. The sculptures and reliefs present a series of structural damages: cracks, fractures with missing parts, and surface stains and dirt. Technical solutions for the restoration of this valuable heritage are suggested.